Pengaruh interpass temperatur terhadap sifat mekanik proses pengelasan SMAW material carbon steel SS400 - Muqsalmina Muqsalmina; Syukran Syukran; Hanif Hanif (Journal of Welding Technology, 2019)
Welding is the process of joints metals by melting through heating. Interpass temperature can influence the rapid slowing of the cooling rate and also determine the percentage of accicular ferrite formation, the slower cooling rate will form more accicular ferrite. Accicular ferrite is a structure that is expected from every welding process because it has more resilient properties. This study aims to determine the effect of temperature interpas on the mechanical properties of the welding process SMAW SS400 carbon steel material. Welding specimens were given variations in interpas temperature treatment namely 100oC, 150oC, and 200oC. The results showed that interpas temperature variation could affect the tensile strength value of welded material. The voltage value on the 100oC interpas specimen is 38.26 Kgf / mm2. The value of the stress in the 150oC interpas specimen is 39.09 Kgf / mm2. The value of the stress in the 200oC specimen is 37.37 Kgf / mm2. The value of the stress without treatment is 32.21 Kgf / mm2. Keywords: Welding, SS400 Carbon Steel, Tensile Test, Interpass TemperatureAbstrak Pengelasan merupakan proses penyambungan logam dengan cara pencairan melalui pemanasan. Interpass temperatur dapat mempengaruhi cepat lambatnya laju pendinginan dan turut menentukan prosentasi terbentuknya accicular ferrite, laju pendinginan lebih lambat akan terbentuk accicular ferrite yang lebih banyak. Accicular ferrite ini merupakan struktur yang diharapkan dari setiap proses pengelasan karena memiliki properties yang lebih tangguh. Penelitian ini bertujuan untuk mengetahui pengaruh interpas temperatur terhadap sifat mekanik proses pengelasan SMAW material carbon steel SS400. Spesimen pengelasan diberi variasi perlakuan temperatur interpas yakni 100oC, 150oC, dan 200oC. Hasil penelitian menunjukkan bahwa variasi temperatur interpas dapat mempengaruhi nilai kekuatan tarik suatu material hasil lasan. Nilai tegangan pada spesimen interpas 100oC adalah sebesar 38,26 Kgf/mm2. Nilai tegangan pada spesimen interpas 150oC adalah sebesar 39,09 Kgf/mm2. Nilai tegangan pada spesimen 200oC adalah sebesar 37,37 Kgf/mm2.Nilai tegangan tanpa perlakuan adalah sebesar 32,21 Kgf/mm2.Kata Kunci : Pengelasan, Carbon Steel SS400, Uji Tarik, Temperatur Interpass